Performance evaluation of the factors influencing Tourists General Satisfaction in the Border Cities. Baneh Border City - Mohammad najarzadeh; Aliakbar bidokhti; jamal moradnejad (تحقیقات کاربردی علوم جغرافیایی)
According to WTTC (World Tourism and Travel Council) forecast tourism contribution of global GDP will be about 6000 billion dollar in 2020 and will create 300 million job Therefore, Tourism could be considered as multidimensional field that response to tourists needs with diversity interests and motivations. Shopping is the most necessity needs and it is the one popular activity for tourists. Border regions facilitate this activity because they have two potentials: appropriate geographical situation and non-favorite economic condition for host community. One of the best and most popular border cities in Iran country is Baneh that placed in the west boundaries between Iran and Iraq country. Region’s Economy  extremely depends on tourism shopping and majority of the host community directly or indirectly involved in that bussiness. Therefore, we can connect tourist's satisfaction with welfare and/or economical condition improvement. As, if it realize positively, region will develop in close future. This paper aims to evaluate performance of factors influencing tourists overall satisfaction in the Baneh border city due to important of development issue. Here, factors divided into two categories: shopping factors and tourism environmental factors. This research has followed a practical object, a descriptive approach with Field- Survey type in the method. Statistical population included tourists who have traveled to baneh city to purchase mainly. Matching to Morgan's table 400 tourist as statistical sample have selected and the questionnaire give to them randomly. The tools for gathering were base on two method, early data (from the field- survey study) and secondary data (from the library studies).   An analysis of the results revealed that, in thematic destinations, in addition to factors related to specific Theme (Subject) that they were more influencing, The tourism environmental factors also can  influence on the tourist total satisfaction . In sumery, this research aims to examine amount of satisfaction factors impact on the overall satisfaction. Finally, suggestions for relevant governmental institutes are provided.